Front Cover: Hydrophobic Magnetic Nanoparticle Assisted One‐Pot Liquid‐Phase Peptide Synthesis (Eur. J. Org. Chem. 40/2017). Issue 40 (10th October 2017) - Okada, Yohei; Asama, Hitomi; Wakamatsu, Hiroki; Chiba, Kazuhiro; Kamiya, Hidehiro
Abstract : The Front Cover shows an experimental procedure for the hydrophobic magnetic nanoparticle assisted one‐pot liquid‐phase peptide synthesis using a soluble tag method. Both couplings and deprotections of the tagged substrate are effectively carried out, even in the presence of the magnetic nanoparticles in a less‐polar solvent. After reaction completion, a polar solvent is added to the reaction mixture to precipitate the desired tagged peptide with the magnetic nanoparticles. The thus formed magnetic precipitate is readily collected by a magnet, enabling an effective one‐pot procedure. More information can be found in theCommunication by Y. Okada et al.